MO208: De Novo Glomerulonephritides Following BNT162B2 COVID-19 Vaccine: A Case Series. (3rd May 2022) - Fornara, Laura; Musetti, Claudio; Guglielmetti, Gabriele; Cantaluppi, Vincenzo
Abstract: BACKGROUND AND AIMS: The development and massive use of mRNA COVID-19 vaccine BNT162b2 has raised new concerns on triggering de novo immune-mediated diseases, in particular rare diseases as glomerulonephritis (GN), even if the security profile is excellent and severe reactions have been rare. In literature few similar cases were recently described [1, 2 ]. We report six cases of newly diagnosed GN after a two-dose regimen of SARS-CoV-2 vaccine, from a single tertiary care institution in Northern Italy. METHOD: We described six cases of de novo GN occurring after massive use of Pfizer-BioNTech BNT162b2 COVID-19 vaccine from March 2021 to December 2021. All cases were biopsy proven. Baseline characteristics and laboratory findings, treatments and outcomes were based on review of medical records. RESULTS: From April 2021, we observed two IgA nephropathies (IgA-N), one membranous nephropathy (MN), one membranoprolipherative GN (MPGN), one acute interstitial nephritis (aTIN) and one minimal change disease (MCD). Of note, one IgA-N presented with diffuse purpura as in IgA-vasculitis. The median age at vaccination was 52.8 years (min–max 18–67) and three (50%) were female; arterial hypertension was the most common comorbidity (50%). Only one subject contracted COVID-19 before vaccine (16.6%). None of the points showed any sign of renal disease before vaccine; at the time of disease onset, the median creatinine was 1.49 mg/dL (min–max 0.6–10.5 mg/dL) and proteinuria 3.0 g/24 h (min–max 0.9–13.8 g/24 h). All cases presented after the second dose (1 day to 6 months thereafter) and three (50%) were within 3 weeks from the vaccine. Of note, the aTIN developed after the vaccine during a long-time therapy with statins and relapsed after a rechallenge with a statin few months later. All the nephropathies were treated as per center practice, with an overall good response (four partial remissions and one complete remission). Given a target population of about 100 000–200 000 residents in our area, we could estimate an incidence rate of 4–8 cases/100 000 patient-years. CONCLUSION: This small series has a lot of limitations including the small number of patients and we probably missed some cases in our area. Furthermore, we could not investigate a causal association, even if the timing of disease onset might be suspicious in three cases and the incidence seemed to be almost twice as the expected in Europe (about 2–4/100.000 patient-years). As for SARS-CoV-2 vaccines, it is likely that the mRNA vaccine will result in a more potent inflammatory stimulus than the one observed after inactivated virus-vaccine: maybe some patients had already a subclinical GN and the vaccine constituted a flare leading to the full-blown disease [3 ].